2003
DOI: 10.1177/107110070302400806
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Arthroereisis for Posterior Tibial Tendon Dysfunction: A Preliminary Report

Abstract: Subtalar arthroereisis by means of implantation of a Kalix endorthesis in the sinus tarsi, with prior correction of the deformity and tendon repair, offers an alternative to bone operations such as calcaneal osteotomies, lengthening the external column, or arthodesis in patients with stage II posterior tibial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 27 publications
(27 reference statements)
5
78
0
15
Order By: Relevance
“…16,27,28 In the absence of advanced degeneration, adult flexible flatfeet have also been recently treated with arthroereisis successfully with growing support. [16][17][18][19][20][21][22] Some authors have also advocated using arthroereisis to protect medial soft tissue reconstructions. 16,17,20,21 Our recent report is the first to describe outcomes of the combined procedure.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…16,27,28 In the absence of advanced degeneration, adult flexible flatfeet have also been recently treated with arthroereisis successfully with growing support. [16][17][18][19][20][21][22] Some authors have also advocated using arthroereisis to protect medial soft tissue reconstructions. 16,17,20,21 Our recent report is the first to describe outcomes of the combined procedure.…”
Section: Resultsmentioning
confidence: 98%
“…15,29 Titanium implants have the highest reported success rates, but carry the risk of needing to be removed. 16,17,[19][20][21][22]28 Future directions should include larger studies of the combine procedure as well as studies comparing various materials. We believe that if the bioabsorbable implants prove to be effective, they may alleviate concerns of needing implant removal.…”
Section: Possible Concerns and Future Of The Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…En revanche, la ténosynovectomie du tendon du muscle tibial postérieur constitue une bonne indication, à condition que les déformations soient réduc-tibles. En général, il est néanmoins nécessaire de pratiquer un temps osseux pour obtenir un bon résultat : l'arthrorise constitue une alternative intéressante [7] (Fig. 2A,B).…”
Section: Alternatives Chirurgicalesunclassified
“…In recent years, clinical studies reported radiographic improvement of foot alignment and pain relief with a subtalar arthroereisis (STA) for the treatment of AAFD (Viladot et al, 2003;Needleman, 2006). Although these findings support the use of a STA, its effect on tibio-talar contact characteristics has not been evaluated in a clinical or cadaver model of a flatfoot.…”
Section: Introductionmentioning
confidence: 97%